Perceiving isn't believing: Divergence in levels of sociolinguistic awareness. (April 2020) - McGowan, Kevin B.; Babel, Anna M.
Abstract: The influence of social knowledge on speech perception is a question of interest to a range of disciplines of language research. This study combines experimental and qualitative approaches to investigate whether the various methodological and disciplinary threads of research on this topic are truly investigating the same phenomenon to provide converging evidence in our understanding of social listening. This study investigates listeners' perceptions of Spanish and Quechua speakers speaking Spanish in the context of a contact zone between these two languages and their speakers in central Bolivia. The results of a pair of matched-guise vowel discrimination tasks and subsequent interviews demonstrate that what people perceive, as measured by experimental tasks, is not necessarily what they believe they hear, as reported in narrative responses to interview prompts. Multiple methodological approaches must be employed in order to fully understand the way that we perceive language at diverging levels of sociolinguistic awareness. (Perception, sociophonetics, sociolinguistics, awareness, Andean Spanish)